2021
DOI: 10.18502/kls.v6i1.8772
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Case Manager Competence and Nurse Burnout in Indonesia

Abstract: This study aims to identify the relationship between case manager competency and nurse burnout in Indonesia. A cross-sectional survey was conducted with 235 nurses in three hospitals located in Jakarta and Tangerang. The questionnaire used in this study comprise of: demographic data; General Self Efficacy Scale; Nurse Manager Competency Scale; and Oldenburg Burnout Inventory. Most respondents experienced emotional exhaustion and disengagement. The case manager’s competence reported low. Analysis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…An investigation aimed to identify the relationship between nurse burnout and case manager competency. The study found that only three sub-competencies had a significant link with emotional exhaustion [35]. Creating conducive work conditions, which ultimately lead to improved nurse outcomes, such as reduced workplace rudeness, requires the leadership of nurse managers, nursing expertise, appropriate staffing, and adequate resources.…”
Section: Conceptualizationmentioning
confidence: 94%
“…An investigation aimed to identify the relationship between nurse burnout and case manager competency. The study found that only three sub-competencies had a significant link with emotional exhaustion [35]. Creating conducive work conditions, which ultimately lead to improved nurse outcomes, such as reduced workplace rudeness, requires the leadership of nurse managers, nursing expertise, appropriate staffing, and adequate resources.…”
Section: Conceptualizationmentioning
confidence: 94%
“…There are few types of research on the relationship between leadership communication competence and employee turnover intention. Research on leaders' communication competence focuses more on their impact on job satisfaction, communication satisfaction, burnout, trust, creativity, and other variables (Delgado & Lubbers, 2021;Lusiyana et al, 2021;Mikkelson et al, 2021;Ulutürk & Tayfun, 2019). These related variables are related to employee turnover intention in some previous studies, for example, job satisfaction and employee turnover intention (Ali & Anwar, 2021;Hefny, 2021;Nguyen & Tran, 2021;Prasetyo & Semarang, 2021), job burnout and employee turnover intention (Gharakhani & Zaferanchi, 2019;Liu & Lo, 2018;Wang et al, 2020;Zhang et al, 2021), trust and employee turnover intention (Brohi et al, 2021;Ozturk et al, 2014;Rafiq et al, 2019;Zeffane & Bani Melhem, 2017).…”
Section: Leadership Communication Competencementioning
confidence: 99%
“…Woo (2020) melakukan meta analisis terhadap studi dan mendapatkan prevalensi global terhadap burnout sebesar 11.23% (Woo et al, 2020). Tay (2014) menemukan prevalensi burnout di sebuah rumah sakit di Singapura sebesar 33.3% (Tay et al, 2014), Di Indonesia sendiri emotional exhaustion ditemukan sebesar 38.3% di dua rumah sakit di Tangerang dan Jakarta (Lusiyana et al, 2021) Jones ( 2015) melakukan studi review dan menemukan 55-58% melaporkan setidaknya satu MNC terjadi (Jones et al, 2015). Menurut Chaboyer (2020) kejadian MNC tidak bergantung kepada negara, jenis rumah sakit, besarnya rumah sakit dan lokasi.…”
Section: Latar Belakangunclassified